2016
DOI: 10.1016/j.ydbio.2016.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell fate in the nephron tubule is mediated by the ETS transcription factors etv5a and etv4 during zebrafish kidney development

Abstract: Kidney development requires the differentiation and organization of discrete nephron epithelial lineages, yet the genetic and molecular pathways involved in these events remain poorly understood. The embryonic zebrafish kidney, or pronephros, provides a simple and useful model to study nephrogenesis. The pronephros is primarily comprised of two types of epithelial cells: transportive and multiciliated cells (MCCs). Transportive cells occupy distinct tubule segments and are characterized by the expression of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 70 publications
0
90
0
Order By: Relevance
“…Previous research from our lab and others has indicated the significant role of RA and Notch in patterning proximal cell fates within the kidney, including the podocyte lineage (Wingert et al, 2007; Bollig et al, 2009; Wingert and Davidson, 2011; Li et al, 2014; Cheng and Wingert, 2015; Marra and Wingert, 2016). Thus, one possible explanation for the dearth of podocytes in zep was a local reduction in RA levels or Notch signaling.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous research from our lab and others has indicated the significant role of RA and Notch in patterning proximal cell fates within the kidney, including the podocyte lineage (Wingert et al, 2007; Bollig et al, 2009; Wingert and Davidson, 2011; Li et al, 2014; Cheng and Wingert, 2015; Marra and Wingert, 2016). Thus, one possible explanation for the dearth of podocytes in zep was a local reduction in RA levels or Notch signaling.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, we next examined whether a deficiency of RA might underlie the abrogation of podocyte development in zep . Previous studies have shown that the nephron patterning defects caused by RA deficiency can be rescued by the addition of exogenous all-trans RA to the embryo media beginning at gastrulation stages (Wingert and Davidson, 2011; Li et al, 2014; Cheng and Wingert, 2015; Marra and Wingert, 2016; Marra et al, 2016). To test whether zep fail to form podocytes due to insufficient RA levels, heterozygous zep zebrafish were mated, and their clutches were treated with varying levels of exogenous all-trans RA to interrogate whether supplementation of this metabolite was sufficient to rescue podocyte numbers in zep mutant embryos.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to WTs, exposure to 1 mM 4-HPR led to an expansion of the PCT, caudal shift of the DE, and a dramatic expansion of the interval between these segments where the PST normally emerges, suggestive of an expanded PST segment (Figure 1D) (Poureetezadi et al, 2014). The observation that molecules which impact the RA pathway were flagged as hits in the screen provided an important positive control for our experimental system, given the well-established effects of RA levels on renal progenitors (Wingert et al, 2007; Wingert and Davidson, 2011; Li et al, 2014; Cheng and Wingert, 2015; Marra and Wingert, 2016; Drummond et al, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…MO sequences and dosages used were: irx3b 5'-ATAGCCTAGCTGCGGGAGAGACATG-3', 1 ng (Wingert and Davidson, 2011); ptger2a MO1 5'-GATGTTGGCATGTTTGAGAGCATGC-3', 3 ng (North et al, 2007); ptger2a MO2 5'-ACTGTCAATACAGGTCCCATTTTC-3', 1.6 ng (North et al, 2007); ptger2a MO3 splice 5'-CAATAAATCTTACTATTAACGGCAG-3', 3 ng; ptger2a MO4 splice 5'-ATGTACACACGGATCTG-AAGAGAAG-3', 3 ng; ptger4a MO1 5'-CGCGCTGGAGGTCTGGAG-ATCGCGC-3', 3 ng (North et al, 2007); ptger4a MO2 5'-CACGGTGGGCTCCATGCTGCTGCTG-3', 3 ng (Cha et al, 2006); ptger4a MO3 splice 5'-CCTGGAACTTACAACAAGCGGGATT-3', 3 ng; ptger4a MO4 splice 5'-TGAGAAACA-CCTGGACCTGCCAGAA-3', 3 ng; ptgs1 MO 5'-TCAGCAAAAAGTTACACTCTCTCAT-3’, 3 ng (North et al, 2007); ptgs2a MO 5'-AACCAGTTTATTCATTCCAGAAGTG-3', 3 ng (Grosser et al, 2002); ptgs1 MO splice 5'-AACTTTCATTGCTC-ACCTCTCATTG-3', 2 ng; ptgs2a MO splice 5'-ATTCAACTTA-CACAACAGGATATAG-3', 2 ng (Yeh et al, 2009), sim1a MO 5'-TCGACTTCTCCTTCATGCTCTACGG-3', 1 ng (Cheng and Wingert, 2015). To assess knockdown efficacy, RT-PCR and sequence analysis was performed as previously described (Marra and Wingert, 2016) and using the following primers, where uppercase letters indicate location in an exon and lowercase indicates primer location in an intron: ptgs1-F1 5'-TTTATTTATTTGCAGCTTTTTCTT-3'; ptgs1-R1 5'-CAGTGTTTGATGAAGTCGGGCTTTC-3'; ptgs2a-F1 5'-CTGAGCTTCTCACACGCATCAAAT-3'; ptgs2a-R1 5'-GGCGAAGAAAGCAAACATGAGACT-3'; ptger2a-F1 5'-AGACCGAGCGTATGCCAATGT- 3'; ptger2a-R4 5'-caggagggctaataattcagactt-3'; ptger2a-F3 5'-ctgtttcagtgatcagtttgt-3'; ptger2a-R7 5'-CCGCAGAGCTATGAGATCAGTC-3'; ptger2a-R8 5'-GCTGAGGATGATGAACACCAAG-3'; ptger4a-F3 5'-ATGGTCATCCTGTTGATCGCC-3'; ptger4a-R2 5'-aatgagagtcctggaacttac-3'; ptger4a-F5 5'-gggtgtagtcatttatgttgagca-3'; ptger4a-R5 5'-CAGGACCGCTTTACGCAGTAAG-3'.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation